Next-Generation Micro-Scale Biochemical Sensing Technologies for Safety Assessment of Edible Materials - Dr. R. Patel (Emerging Frontiers Library for The American Journal of Interdisciplinary Innovations and Research, 2026)
The increasing complexity of global food supply chains and the rising prevalence of chemical adulterants, contaminants, and pathogens necessitate advanced sensing technologies capable of rapid, precise, and real-time detection. Micro-scale biochemical sensing technologies have emerged as a transformative solution, integrating nanomaterials, microelectromechanical systems (MEMS), and biosensing mechanisms to enhance food safety assessment. This study presents a comprehensive technical and analytical exploration of next-generation micro-scale biochemical sensors, focusing on their structural design, functional mechanisms, and applicability in edible material safety evaluation. The research synthesizes insights from interdisciplinary domains, including nanobiosensors, magnetic field sensing technologies, and microfabrication techniques. Particular emphasis is placed on nano-enabled biosensing approaches that leverage high surface-area-to-volume ratios and enhanced signal transduction capabilities for detecting trace-level contaminants. The study critically evaluates sensing platforms such as electrochemical biosensors, optical sensors, and magnetometer-based detection systems, highlighting their operational principles, advantages, and constraints. Drawing from existing literature, including advancements in nanobiosensor applications for food safety (Agarwal et al., 2025), the paper identifies critical challenges such as sensitivity limitations, environmental interference, calibration complexities, and scalability issues. Furthermore, it establishes a conceptual framework linking micro-scale sensor architectures with real-world deployment scenarios, including on-site food inspection, supply chain monitoring, and consumer-level testing devices. The findings suggest that integrating hybrid sensing modalities and improving signal processing algorithms can significantly enhance detection accuracy and reliability. However, practical implementation remains constrained by cost, durability, and standardization barriers. The study concludes by proposing future research directions focused on smart sensing systems, AI-integrated analytics, and sustainable sensor fabrication. This paper contributes to the growing body of knowledge on food safety technologies by providing a technically rigorous and analytically grounded evaluation of micro-scale biochemical sensing systems, emphasizing their role in ensuring the integrity and safety of edible materials in modern food ecosystems.